Life as a Stranger: Experiences of Labor Migrants from Lesotho - Moletsane, Malilimala; Coetzee, Jan K.; Rau, Asta (Qualitative Sociology Review, 2017)
Drawing on in-depth interviews with nine Basotho labor migrants in Bloemfontein, this article examines their experiences of being a stranger by exploring their accounts of everyday life. Literature on migration studies confirms that migrants face numerous challenges in destination areas, and South Africa is no exception in this regard. The major concerns expressed by the research participants are harassment by the police, hostility from the local citizens, poor living conditions, exploitation by employers, the language barrier, and difficulty in accessing public services. This article argues that these constraints make it difficult for migrants to establish a sense of belonging. Instead, they have a sense of being outsiders and strangers in Bloemfontein.